Centralization of National Food Authority and Marginalization of Local Capacity: An Analysis of Decentralization Implications for Regional Food Security - Aqshal Dwi Raldo; Larasati Sukmadewi Wibowo (Universitas Negeri Gorontalo, 2025)
The establishment of the National Food Agency through Presidential Regulation Number 66 of 2021 reflects a trend toward centralization of food authority that contradicts the decentralization principle enshrined in Law Number 23 of 2014 concerning Regional Governance. This centralization creates excessive authority concentration at the national government level and threatens the capacity of regional governments to manage local food security autonomously. This research aims to: (1) analyze the constitutional implications of food authority centralization on regional autonomy; (2) evaluate the capacity of regional governments in implementing local food policies; and (3) formulate recommendations for regulatory and policy harmonization between national and regional governments. The research employs legal document analysis (regulations and food policies), a case study of West Java Province as a best practice in food decentralization, and comparative analysis of regional autonomy implementation in the food sector. The findings demonstrate that the West Java Regional Government has exhibited significant capacity through initiatives including mainstreaming of local food, urban farming implementation, hydroponics technology deployment, and empowerment of local farmers—thereby proving that food authority decentralization is not merely feasible but essential for sustainable food security. The research recommends: (1) harmonization and synchronization of national-regional food regulations to prevent jurisdictional conflicts; (2) strengthening of coordination mechanisms and continuous evaluation systems; and (3) redistribution of food authority according to the subsidiarity principle and capacity-based allocation to prevent constitutional regression and strengthen local food sovereignty.